Anaphylactic Reactions in People Taking Amophophallus Paeoniifolius (Suweg) - Roykhan Prayudianto (Rifa'Institute, 2022)
Systemic anaphylactic reactions are a rare condition with a prevalence of around 1.6-5.1%. Based on the latest epidemiological data the ratio of fatal anaphylactic reactions is approximately 1%. To diagnose anaphylaxis, sampson criteria are used. Anaphylaxis is a severe, potentially fatal, systemic allergic reaction that occurs suddenly after contact with an allergycausing substance. Anaphylaxis, it was acknowledged that no criteria will provide 100% sensitivity and specificity, but it was believed that the criteria proposed are likely to capture more than 95% of cases of anaphylaxis. Anaphylaxis itself occurs in 15 of 10,000 patients and is characterized by acute reactions, with diffuse erythema, pruritus, urticaria, angioedema, bronchospasm, laryngeal edema, hyperperistalsis, hypertension, cardiac arrhythmias, hemolytic anemia. Most symptoms develop quickly (five to 30) minutes after exposure. A 44-year-old with an anaphylactic reaction has been reported. The administration of epinephrine 0.3-0.5 cc deltoid IM and general management of anaphylaxis in the initial acute condition of anaphylactic reaction is given to the patient.